Historical Data Provide Important Context for Understanding Declines in Cutthroat Trout. (18th April 2021) - Nordberg, Brittany J.; Mandeville, Elizabeth G.; Walters, Annika W.; Burckhardt, Jason C.; Wagner, Catherine E.
Abstract: We used historical stocking and population survey records of Yellowstone Cutthroat Trout Oncorhynchus clarkii bouvieri and other salmonids in the North Fork Shoshone River drainage, Wyoming to summarize fish stocking history and population trends. Based on 98 years of historical records, we found that despite extensive stocking of Yellowstone Cutthroat Trout and minimal stocking of nonnative salmonids after about 1950, populations of wild Yellowstone Cutthroat Trout declined relative to those of nonnative salmonid species. The timing of increases in nonnative salmonids (1970s) did not coincide with their period of most intensive stocking (1935–1950). It is plausible that Yellowstone Cutthroat Trout populations persisted because of high levels of supplemental stocking from 1935 to 1965 and declined with reduced stocking efforts in the 1970s, thereby allowing the increase of introduced nonnative salmonids. The establishment of nonnative salmonids likely further reduced stocking success of Yellowstone Cutthroat Trout due to competition and hybridization. This study demonstrates that an understanding of long‐term stocking records and population survey data can be useful for developing and implementing successful management frameworks for the conservation of imperiled fish populations across the United States.